TYPES OF LANGUAGE FUNCTION FOUND IN THE PERFECT DATE MOVIE - Ni Made Wahyuni; I Gusti Bagus Wahyu Nugraha Putra; Putu Devi Maharani (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
This study is concerned with the types of language functions in The Perfect Date Movie. This study is aimed to answer the research problems, which are: (1) to find out the types of language functions used by the main character of The Perfect Date movie and (2) to analyse the types of languages style are found in utterances produced by the main character of The Perfect Date movie. It used a descriptive qualitative method to identify data. Types of language function and language style was described according to the theory proposed by Tillit and Bruder (1985). The result of this study was found 75 data. The 75 data were classified into eleven types of language function which found in the utterances produced by the main character and three types of language styles. The types of language function which found eleven types of language function proposed by Tillit and Bruder (1985) were twelve of openings, pre-openings, and closings type, four data of introduction and addressing system type, seven data of invitations type, eight data of thanking people and replying thanks type, three data of apologizing type, ten data of giving compliments and replying complements type, two data of getting people’s attention and interrupting, two data of agreeing and disagreeing type, seven data of controlling the conversation type, and two data of getting information e language style which was found were ten data of formal expression, thirty nine data of informal expression and twenty six data of neutral expression. The most types of language function found in this study is getting information because the main character feel free and more comfortable expressing their emotional in a language.